The Leaf Bacterial Microbiota of Female and Male Kiwifruit Plants in Distinct Seasons: Assessing the Impact of Pseudomonas syringae pv. actinidiae - Ares, Aitana (2021)
The Pseudomonas syringae pv. actinidiae pandemic has been compromising the production of the kiwifruit industry in major producing countries. Abiotic factors and plant gender are known to influence the disease outcome. To better understand their impact, we have determined the diversity of the leaf bacterial communities using the V5-V6 region of the 16S ribosomal RNA gene amplicon on the Illumina MiSeq sequencing platform. Healthy and diseased female and male kiwifruit plants were analyzed in two consecutive seasons: Spring and autumn. This work describes whether the season, plant gender, and presence of P. syringae pv. actinidiae can affect the leaf bacterial community. Fifty bacterial operational taxonomic units were identified and assigned to five phyla distributed by 14 different families and 23 genera. The leaves of healthy female and male kiwi plants share most of the identified bacterial populations, which undergo major seasonal changes. In both cases, a substantial increase of the relative abundance of genus Methylobacterium is observed in autumn. The presence of P. syringae pv. actinidiae induced profound changes on leaf bacterial community structures, translated into a reduction in the relative abundance of previously dominant genera that had been found in healthy plants; namely, Hymenobacter, Sphingomonas, and Massilia spp. The impact of P. syringae pv. actinidiae was less pronounced in the bacterial community structure of male plants in both seasons. Some of the naturally occurring genera have the potential to act as antagonists or as enhancers of the defense mechanisms, paving the way for environmentally friendly and sustainable disease control.